Funções exercidas e relações retóricas sinalizadas pelas estratégias de parentetização e de repetição em elocuções formais - Ganasino, Monique Bisconsim (2016)
The aim of this study is investigating the function and rhetorical relations settled by bracketing strategies and repetition in spoken language (formal utterances). Also, it seeks to present the main features of these strategies related to production, formal marks, distribution and construction. This research has as its theoretical basis the Functionalism and the Theory of Rhetoric Structure (Rhetorical Structure Theory - RST), which has as its object of study the relationships established between the parts of the text. It is believed that the design of spoken language, which also underlies this research, speaking and writing are not watertight arrangements, or organize themselves within a typological continuous, even though there are specific characteristics of speech: the non-planning, which tends to build a fragmented oral text, with a discursive flow discontinued; pragmatic pressures, which can lead the speaker not to use the traditional syntax. These features are stated in the spoken text in form of hesitations, truncation, false starts and corrections, among others. The corpus of this research consists on formal utterances (five classes of higher education) belonging to Funcpar (Functionalists Research Group from the North / Northwest of Paraná). Classes are transcribed in accordance to the established rules by the Urban Culture Standard Project (NURC) and segmented into intonation units. Quantitative analysis of bracketing corpus shows that most of these occurrences manifests without a formal marker and its main functions: to test the understanding of the speaker, to establish the comprehensibility of the topic and to evoke shared understanding of the topic. In addition, there is a single rhetorical relation: a parenthetical. As for the repetitions, it may be noticed that these, in the corpus, are produced by the teacher only. Ie they are auto-repetitions. Furthermore, there was a higher frequency of distant repetitions than adjacent ones. As for building repetitions (full or variation), it was found almost the same amount in the research corpus, and its most common functions are: syntactic amalgams, intensification, rheme - the theme and driving and maintenance of the topic. Also there is a unique rhetoric relationship signaled by repetition: reassurance. However, this relationship manifests itself into two different ways: with iconic motivation (boost function) or structure of repetition (list function). Through this paper, it is expected to be used to cooperate on other research involving the theory of RST and the formulation of strategies of spoken text, especially the bracketing and repetition.